Synthesis and Properties of Poly(1,8-Diaminonaphthalene) using Tetravalent Cerium as Oxidant - Zhang, J.L.; Wang, H.; Tu, X.C.; Wu, W.J.; Huang, L. (Asian Journal of Chemistry, 2012)
The poly(1,8-diaminonaphthalene) (P18DAN) was readily synthesized by chemical oxidative polymerization. The structure of Ce3+-P18DAN was characterized by the spectra of FT-IR, Raman, UV-VIS and WXRD. Red-shifted change for the quinoid and benzenoid structure stretching vibration are observed in IR and Raman spectra after doping Ce3+ ions and a new UV absorption peak presents at 610 nm. The results show that the interaction had occurred between Ce3+ ions and amino or imine groups on P18DAN backbone. A more keen-edged diffractive peak is exhibited at 2q = 24.3º for Ce3+-P18DAN in WXRD, while the peak at 16.9º ascribed to the periodicity parallel chains disappears. Comparing to H+-P18DAN, the excitation and emission peaks centered at 388 nm and 512 nm, respectively, have a red-shifted for 51 nm and 107 nm. Additionally, the conductivities of P18DAN are increased from 2.37 × 10-6 to 5.70 × 10-4 S cm-1 after doping Ce3+ ions, suggesting that the degree of electrons delocalization are improved by complexing with Ce3+ ions.